2021
DOI: 10.1007/s11575-021-00453-y
|View full text |Cite
|
Sign up to set email alerts
|

Achieving the Paradox of Concurrent Internationalization Speed: Internationalizing Rapidly in Both Breadth and Depth

Abstract: In this paper, we draw on the notions of breadth and depth of internationalization speed in an attempt to examine the performance implications for multinational enterprises (MNEs) that rapidly and concurrently internationalize in new and existing foreign markets. Specifically, we examine the organizational paradox which suggests that firms which grow internationally by concurrently expanding rapidly in both new foreign markets (breadth) and in foreign markets they currently operate (depth), are better off than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 127 publications
0
11
0
Order By: Relevance
“…The mechanism responsible for the ability of the IGF to optimally enter the reconfiguration stage is the speed of internationalization. Batsakis and Theoharakis (2021) observed that concurrent internationalization breadth and depth at high speed can result in high performance in large multinational organizations. However, multinational organizations already have MBR 32,3 experience abroad, and the same study suggests that CEOs with international experience and training are more likely to accept paradoxical tensions.…”
Section: Strategic Internationalization Decisions and Reconfiguringmentioning
confidence: 99%
“…The mechanism responsible for the ability of the IGF to optimally enter the reconfiguration stage is the speed of internationalization. Batsakis and Theoharakis (2021) observed that concurrent internationalization breadth and depth at high speed can result in high performance in large multinational organizations. However, multinational organizations already have MBR 32,3 experience abroad, and the same study suggests that CEOs with international experience and training are more likely to accept paradoxical tensions.…”
Section: Strategic Internationalization Decisions and Reconfiguringmentioning
confidence: 99%
“…From the point of view of competitiveness, it is important for an entrepreneur that customs control standards correspond to modern business conditions in international trade in goods. Therefore, it is important that control activities are carried out in a clear, stable, transparent and Consistent rules in all countries Control times should be kept to a minimum There should be no downtime or interruption in the flow of goods Easy access to information and no additional costs At the same time entrepreneurs acting in accordance with the law expect effective sanctions from the customs authorities in relation to persons who knowingly ignore the rules or use control tools in order to achieve a quick profit or competitive advantage (European Parliament, 2019;Cha et al, 2023;Batsakis, Theoharakis, 2021). In order to increase the competitiveness of enterprises, states must create a favorable environment for economic operators, so customs control should be the lowest possible burden and, of course, should not hinder business by creating additional costs in trade.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fourth, digital platform-based transactions are quite different from the others. Key attributions of e-commerce firms' growth are their fast internationalization speed and the extensive breadth of operations across different areas (Batsakis & Theoharakis, 2021;Swoboda & Sinning, 2022). Especially, sharing economy firms set the protocols and algorithms with the formal programming language for specific digital platforms (e.g., Airbnb apps, Uber apps, etc.)…”
Section: The Attributes Of Digital Platform-based Transactions From T...mentioning
confidence: 99%